2016
DOI: 10.1177/0021998316658536
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of hybrid conductive fillers on the electrical properties of carbon fiber pultruded polypropylene/polycarbonate composites prepared by injection molding

Abstract: In this study, the effects of filler characteristics and composite preparation methods on the morphology, mechanical property, electrical conductivity, and electromagnetic interference shielding effectiveness of the polypropylene/polycarbonate (70/30, wt%)/hybrid conductive filler composites were investigated. Nickel-coated carbon fiber (NCCF) was used as main filler and TiO2, multi-walled carbon nanotube, and graphite were used as second fillers in the composites. The pultruded NCCF/polypropylene composite wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Dielectric materials and their composites have also been used in blocking incoming EM waves. 406–437 Lu et al 406 studied the thickness dependence variation of reflection loss against ε ′ and ε ′′ (Fig. 18(a)) and microwave absorption properties of the composites loaded with 10 wt% ZnO@MWCNTs vs. the frequency and thickness at different temperatures (Fig.…”
Section: Dielectric Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dielectric materials and their composites have also been used in blocking incoming EM waves. 406–437 Lu et al 406 studied the thickness dependence variation of reflection loss against ε ′ and ε ′′ (Fig. 18(a)) and microwave absorption properties of the composites loaded with 10 wt% ZnO@MWCNTs vs. the frequency and thickness at different temperatures (Fig.…”
Section: Dielectric Materialsmentioning
confidence: 99%
“…The hybrid fillers consisting of nickel-coated carbon fiber (5.2 vol% or 20 wt%) and TiO 2 (1.2 vol% or 5 wt%) on incorporation in the polypropylene/polycarbonate (70/30) composite displayed superior performance (EMI SE: 51.6 dB). 423 This was due to the high dielectric constant with dominant dipolar polarization and the synergistic effect of TiO 2 . The EMI SE of the PP/Ni-coated carbon fiber (15 wt%) with the MWCNT (3 wt%), carbon black (3 wt%) and TiO 2 (3 wt%) at a frequency of 0.5 GHz were found to be 35.9, 38.5, 43.3, and 45.2 dB, respectively.…”
Section: Dielectric Materialsmentioning
confidence: 99%
“…Also, there was cured adhesive in the conductive network, which could have formed a fragile interface with low conductivity between any two carbon fibers, hindering the movement of electrons in the conductive network. Under the synergistic effect of the electric field and heat field formed after power was applied, the fragile interface in the electric heating layer broke down (Yang et al 2000), which increased conductive pathways. More pathways in the electric heating layer lead to better conductivity (Hung et al 2015).…”
Section: Analysis Of Resistance Stability In the Heating Processmentioning
confidence: 99%
“…Furthermore, the insulation and water resistance needed to be strengthened. Epoxy resin prepreg was used by Yang et al (2000) to improve the insulation performance of carbon fiber electric heating membrane. The prepreg with enhanced glass fiber inside, bonded with wooden substrate, was easily stressed, leading to deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The technique based on dispersion of two or more conductive fillers into an insulating polymer matrix has been used to improve the composite properties. In fact, some works in the open literature demonstrate better EMI SE results when conductive fillers with different geometries are combined into an insulating polymer matrix (Zhang et al, 2012(Zhang et al, , 2018Szeluga et al, 2015;Jang et al, 2016;Kumar et al, 2017;Wu et al, 2017). For instance, Sharma et al (2016) and Kuester et al (2017) observed higher EMI SE values for hybrid composites containing CNT/GR and CNT/GnP, respectively, than those found for composites containing the individual fillers.…”
Section: Introductionmentioning
confidence: 97%